Ungkapan 100% Katolik 100% Indonesia dan Kaitannya dengan Peribadatan Umat di Tangerang - Brigita, Agnes; Fauzi, Agus M. (Hanifiya: Jurnal Studi Agama-Agama, 2022)
The Catholic Church during this pandemic also urges its followers to comply with all government policies and changes in the social conditions of the people which have changed a lot and have caused many changes in people's attitudes as well as to continue their lives, leading to the birth of the phrase "100 Catholics 100% Indonesian". The purpose of this study is to find out what is the relationship between these expressions and the worship and unity of Catholics in Tangerang. The research method used is through research and the type of research carried out is using quantitative research. The theory that can be used in this research is the social behavior paradigm proposed by Mc. Guire about the role of religion in shaping the value system within the individual, because in this theory the main issue raised is about the behavior of the individual himself. It can be described by the spiritual interests of the people and the interests of the government in dealing with this pandemic. The results of this study found a relationship between these expressions and the worship activities of Catholics. The existence of this expression is used as an invitation for the people to obey and carry out what is the government's policy, without leaving their spiritual life.